Heart rate cost as a tool for monitoring recovery between acute training sessions - José Morais Souto Filho; Milton Rocha de Moraes; Patrício Lopes de Araújo Leite; Larissa Alves Maciel; Andréa Cândida Arruda Andrade Rezende; Thiago dos Santos Rosa; Fabiana Andrade Machado; Sergio Rodrigues Moreira; Ricardo Yukio Assano; Marcelo Magalhães Sales; Herbert Gustavo Simões (Human Movement)
Purpose Effective recovery monitoring is crucial to optimise performance and prevent overreaching, injuries, and overtraining. This study evaluated the heart rate cost (HRC) during submaximal running as a simple, non-invasive, and costeffective tool to assess recovery after a high-intensity training session.